2021
DOI: 10.3390/cancers13050996
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Impairment at the Host-Microbiota Interface in Colorectal Cancer

Abstract: Colorectal cancer (CRC) initiation is believed to result from the conversion of normal intestinal stem cells (ISCs) into cancer stem cells (CSCs), also known as tumor-initiating cells (TICs). Hence, CRC evolves through the multiple acquisition of well-established genetic and epigenetic alterations with an adenoma–carcinoma sequence progression. Unlike other stem cells elsewhere in the body, ISCs cohabit with the intestinal microbiota, which consists of a diverse community of microorganisms, including bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 201 publications
(226 reference statements)
0
30
0
Order By: Relevance
“…Bacteroides vulgatus and Bacteroides fragilis were isolated from patients suffering from Crohn’s disease, in addition Bacteroides fragilis was associated with intra-abdominal abscesses, appendicitis, and inflammatory bowel disease. As thoroughly reviewed by us in Marzano et al, 2021 (19) we highlighted the interaction between some species, including Bacteroides fragilis and the colorectal cancer, suggesting the identification of the gut microbiota biomarkers with diagnostic, prognostic or predictive significance, as well as the the possibility of intestinal microbiota modulation to prevent cancer or enhance the effect of specific therapies. In this study, we found Bacteroides vulgatus and Bacteroides uniformis were associated to F samples.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Bacteroides vulgatus and Bacteroides fragilis were isolated from patients suffering from Crohn’s disease, in addition Bacteroides fragilis was associated with intra-abdominal abscesses, appendicitis, and inflammatory bowel disease. As thoroughly reviewed by us in Marzano et al, 2021 (19) we highlighted the interaction between some species, including Bacteroides fragilis and the colorectal cancer, suggesting the identification of the gut microbiota biomarkers with diagnostic, prognostic or predictive significance, as well as the the possibility of intestinal microbiota modulation to prevent cancer or enhance the effect of specific therapies. In this study, we found Bacteroides vulgatus and Bacteroides uniformis were associated to F samples.…”
Section: Discussionmentioning
confidence: 80%
“…The alteration in the stable composition of the gut microbiota, a condition known as dysbiosis, leads to a disruption of homeostasis with the host. Different types of dysbiosis are associated with various harmful effects on human health and long-term consequences may induce a wide range of diseases including inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), diabetes mellitus, obesity, and colorectal cancer (15)(16)(17)(18)(19)(20). Understanding the composition of the gut microbiota, throughout the GI tract, and the role that microbial populations can play in human intestinal health and disease can be critical for achieving a possible early diagnosis but also for the eventual development of appropriate therapeutic approaches based on the gut microbiota manipulation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of cancer microbiota, a variety of metabolites may originate from bacterial, fungal and host metabolisms, or cometabolic networks between the host and microbial communities. In order to circumvent the compositional nature of metabarcoding data in the metagenomics strategy, a multi system-based approach (integrative multi-omics) could broaden our knowledge of the function of the interplay of microbial communities and cancer stem cells in carcinogenesis [71]. Llyod-Price et al used an innovative multi-omics network analysis of ten omics data (metagenomic, metabolomic, metatrascriptomic data, etc.)…”
Section: Limitations and Challenges In Sample Collection And Laboratory Methodologiesmentioning
confidence: 99%
“…Finally, a growing body of evidence has suggested that there is a significant interplay between gut microbiota and the host at the intestinal stem cell niche level, where microbiota may affect directly or indirectly the proliferation, differentiation and reprogramming of the intestinal stem cells and their transformation to cancer stem cells, resulting in CRC initiation and progression through a plethora of mechanisms reviewed elsewhere [71]. The totality of studies has focused on the role of gut bacteria on the abnormal reprogramming of intestinal and cancer stem cells without examining the role of fungi in this interplay.…”
Section: The Interplay Of Gut Microbiome and Mycobiome In Colon Physiology/pathology And Crc Pathogenesismentioning
confidence: 99%
“…Indeed, African Americans with a higher risk of CRC have a higher concentration of secondary bile acids in their feces in comparison with rural Africans [11,126]. Emerging experimental evidence supports that a high level of secondary bile acids is carcinogenic to the colon, for example, by driving malignant transformations in cancer stem cells [127,128]. As an example, the HFD diet appreciably increased the levels of tauro-β-muricholic acid (T-βMCA) and DCA in Apc Min/+ mice, which markedly impaired intestinal integrity and promoted tumor growth.…”
Section: Figurementioning
confidence: 99%